Innovative Education and Training in high power laser plasmas (PowerLaPs) for plasma physics, high power laser–matter interactions and high energy density physics – theory and experiments. (2019) - Pasley, John; Andrianaki, Georgia; Baroutsos, Andreas; Batani, Dimitri; Benis, Emmanouil P.; Borghesi, Marco; Clark, Eugene; Cook, Donna; D'Humieres, Emmanuel; Dimitriou, Vasilios; Dromey, Brendan; Ehret, Michael; et al.
Abstract : The Erasmus Plus programme 'Innovative Education and Training in high power laser plasmas', otherwise known as PowerLaPs, is described. The PowerLaPs programme employs an innovative paradigm in that it is a multi-centre programme where teaching takes place in five separate institutes with a range of different aims and styles of delivery. The 'in class' time is limited to four weeks a year, and the programme spans two years. PowerLaPs aims to train students from across Europe in theoretical, applied and laboratory skills relevant to the pursuit of research in laser–plasma interaction physics and inertial confinement fusion (ICF). Lectures are intermingled with laboratory sessions and continuous assessment activities. The programme, which is led by workers from the Technological Educational Institute (TEI) of Crete, and supported by co-workers from the Queen's University Belfast, the University of Bordeaux, the Czech Technical University in Prague, Ecole Polytechnique, the University of Ioannina, the University of Salamanca and the University of York, has just completed its first year. Thus far three Learning Teaching Training (LTT) activities have been held, at the Queen's University Belfast, the University of Bordeaux and the Centre for Plasma Physics and Lasers (CPPL) of TEI Crete. The last of these was a two-week long Intensive Programme (IP), while the activities at the other two universities were each five days in length. Thus far work has concentrated upon training in both theoretical and experimental work in plasma physics, high power laser–matter interactions and high energy density physics. The nature of the programme will be described in detail and some metrics relating to the activities carried out to date will be presented.